- The Effect of The Electronic Control on Staff Performance -A field Study on Staff of Jeddah Passports Department - Al Talhan, Ahmed Hussein; Khawaldi, Kamal Taher (Journal of Economic, Administrative and Legal Sciences, 2018)
The main objective of this study was to illustrate the impact of the electronic control on the staff performance among employees in Jeddah passports department. The study used the descriptive analytical method. A random sample was taken from the study group. A questionnaire was designed as a data collection tool and distributed to 113 employees. The results of the study found the presence of an effect for the electronic control on staff performance. Also, the study found that the financial and technology difficulties effect on the staff performance. On the other hand, there is not any effect of the administrative and human difficulties on the performance. In the light of the results reached, the study recommended various advice, first, necessity of provide electronic control’s devices and maintenance them because of its positive effect on the performance. Second, taking advantage of modern technology to develop electronic control. Finally, providing the necessary financial resources for the application of electronic control.